Arterial pCO2 prediction using saphenous pCO2 in healthy mechanically ventilated dogs - Ghilardi, Sara; Gamba, Davide; Zanaboni, Anna Maria; Brambilla, Paola G.; Casarrubea, Antonio; Drummer, Pauline; Balsamino, Martina; Ghezzi, Dario; Ricci, Cristina; Caristi, Danilo; Bussadori, Claudio M.; Ravasio, Giuliano (Frontiers in Animal Science, 2024)
Introduction: Arterial blood gas analysis is the gold standard for the assessment of oxygenation, ventilation, and metabolic status in dogs; however, its execution is difficult and painful. Therefore, venous blood gas analysis is used in its replacement for the assessment of the metabolic status, but it is not clear whether it can be used to assess respiratory function, too. This study aimed at: 1) comparing jugular and saphenous pH and partial pressure of carbon dioxide (pCO2) with the correspondent arterial pH and pCO2 (paCO2) in healthy dogs during general anesthesia; 2) clarifying whether the arterial-venous relationship is better expressed in jugular or saphenous blood samples; 3) mathematically transforming venous pCO2 (pvCO2) and evaluating whether the calculated values more accurately agree with paCO2. Methods: Ninety dogs were included and randomly divided into three groups: Group 1 - arterial vs jugular; Group 2 - arterial vs saphenous; Group 3 - arterial vs jugular vs saphenous blood gases. Each group counted 30 dogs. Pearson correlations were calculated. Bland-Altman plots were generated to describe the agreement between venous and arterial values; clinical limits for pH and pCO2 set by the authors were, respectively, ± 0.1 and ± 2.5 mmHg. Univariate linear regression was applied for predicting paCO2 from pvCO2. Results: Saphenous samples showed strong positive correlations with arterial samples for both pCO2 and pH. Pearson  values were stronger for pH than for pCO2. Bland-Altman plots showed good agreement between venous and arterial pH, and poor agreement between pvCO2 and paCO2 for both jugular and saphenous samples. Results suggested that saphenous pvCO2 is preferable with respect to jugular as predictor of paCO2. The transformation of saphenous pvCO2 through univariate linear regression produced a model for predicting paCO2; a Bland-Altman plot assessed the transformed pvCO2 agreement with paCO2. Discussion: In healthy, anesthetized, mechanically ventilated dogs, variations of pH between venous and arterial values are clinically acceptable. Venous and arterial blood gases cannot be interchanged for the evaluation of pCO2. Saphenous pvCO2 is to be preferable to jugular pvCO2 as predictor of paCO2. A formula for the estimation of predicted paCO2 from saphenous pvCO2 is proposed.